If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3 + -4(z + 1) = 3z + -1(z + 2) Reorder the terms: 3 + -4(1 + z) = 3z + -1(z + 2) 3 + (1 * -4 + z * -4) = 3z + -1(z + 2) 3 + (-4 + -4z) = 3z + -1(z + 2) Combine like terms: 3 + -4 = -1 -1 + -4z = 3z + -1(z + 2) Reorder the terms: -1 + -4z = 3z + -1(2 + z) -1 + -4z = 3z + (2 * -1 + z * -1) -1 + -4z = 3z + (-2 + -1z) Reorder the terms: -1 + -4z = -2 + 3z + -1z Combine like terms: 3z + -1z = 2z -1 + -4z = -2 + 2z Solving -1 + -4z = -2 + 2z Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '-2z' to each side of the equation. -1 + -4z + -2z = -2 + 2z + -2z Combine like terms: -4z + -2z = -6z -1 + -6z = -2 + 2z + -2z Combine like terms: 2z + -2z = 0 -1 + -6z = -2 + 0 -1 + -6z = -2 Add '1' to each side of the equation. -1 + 1 + -6z = -2 + 1 Combine like terms: -1 + 1 = 0 0 + -6z = -2 + 1 -6z = -2 + 1 Combine like terms: -2 + 1 = -1 -6z = -1 Divide each side by '-6'. z = 0.1666666667 Simplifying z = 0.1666666667
| 0.50(x+2)+0.75(x+4)=x+5 | | x^2+64-361=0 | | .234=x/6.99*10^-4-x | | 2(11x+28)= | | 10x-3y=-16 | | 4n^3=6n | | 4ln(x-8)-3=13 | | 1.07=3.21 | | -8f=-8 | | 13p=8 | | 4(x-1)-9=6x-2(5+x) | | -6a+5=-a+-3 | | .2344=x/((6.99x10^-4)-x) | | 25*cos(x/50) | | 4(d-3)=23 | | 6x+4x-2x+5x= | | 4-2n=5+1n | | =-20x^2+380x+3600 | | .25x+.75+.75=4 | | (18-2x)(15-2x)x=270 | | -6(3v-4)=96 | | 6+2n=4-3n | | 9x-12xy= | | 9.9=-0.01x^2+0.25x+9.44 | | an=-50+15(n-1) | | 4/20=10/n | | M(x)=7ln(x^7+5x^3)-4x^10 | | (11x+-8)+7(x+-1)= | | 14/20=t/50 | | f(x)=5ln(11/x) | | 69x^2+21x+49=0 | | 0=-16x^2+1280x-19200 |